The Life-Story and reflections upon being an English regional tutor at Santo Tomas University from CAU Chiquinquirá: Teaching practices and experiences in a regional context. (2019)
This project aims to understand the socio-academic experiences and reflections about English teaching practices and experiences in the particular context in which the English tutor teaches in order to understand how the voice of the tutor portrays the social and regional context in relation to the experience of being an English teacher of the Licenciatura en Lengua Extranjera Inglés (LLEI) in such environment. The present study makes part of the study of the English language and its contexts research field and it is framed under the Understanding and characterizing EFL in the LLEI: experiences and phenomena in the pre-service teachers’ educational contexts macro-project, which is focused on giving voice to the LLEI realities: life stories and experiences. For this purpose, this research is focused on the life-story of Yolanda Duarte, a regional English teacher who works as an English tutor at Universidad Santo Tomás at CAU Chiquinquirá. Thus, this story-life research could lead future teachers and researchers to a better comprehension of the socio-academic experiences and daily life of the regional English teacher. Yolanda’s stories are shaped by lifelong personal and community narratives, therefore narrative research allows me to present her experiences and reflections holistically in all its complexity and richness. This project applies concurrent interviewing and narrative frames, in which participants may recount their past history of language learning, as well as learning experiences and incidents that take place during the period of data collection.